Manifestasi Simbolisasi Semangka: Membongkar Konstruksi Makna dan Resistensi Algoritmik dalam Solidaritas Palestina di Indonesia (Studi Kasus Politik Redaksi Republika dan Edu-Fashion MCDC) - Veranisah Nasution (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the resurgence of the watermelon symbol (Citrullus lanatus) as an instrument of civil resistance and transnational solidarity with Palestine in Indonesia following the escalation of the conflict on October 7, 2023. Unlike conventional social movement studies, this research situates the watermelon symbol within the context of hybrid warfare, involving the hegemony of digital platform algorithms and the political economy of media. Using a qualitative approach with Critical Discourse Analysis based on Norman Fairclough’s model, the study analyzes two strategic actors: the Islamic mass media Republika and the creative industry brand MCDC (Muslim Cloth Da’wah Center). The findings reveal that the watermelon symbol functions as a strategy of semiotic camouflage to bypass algorithmic censorship such as shadow-banning on platforms like Meta and TikTok. Republika employs this symbol as a tactic of editorial survival amid the pressures of the global advertising economy while reinforcing its identity as a media umat. Meanwhile, MCDC transforms the symbol into an edu-fashion commodity supported by barcode technology as a form of cultural retaliation and psychological therapy addressing the collective guilt of Indonesia’s Muslim middle class. Consequently, the watermelon symbol undergoes a process of glocalization of meaning within the contemporary digital sphere